Brasileirinho sergipanus sp. nov. (Crustacea: Isopoda: Calabozoidea), new cave-restricted species from the karst of Sergipe State, Brazil - Cardoso, Giovanna Monticelli; Bento, Diego De Medeiros; Ferreira, Rodrigo Lopes (Zootaxa, 2025)
A new stygobitic calabozoid species, Brasileirinho sergipanus sp. nov., is described. This species is exclusively found in the Toca da Fumaça cave, located within the limestones of the Canudos Geological Formation in Sergipe state, northeastern Brazil. The new species is characterized by several distinctive traits, notably the reduced and simple shape of male pleopod 1, in contrast to the biarticulate, thick lamellar structure with an acute angle observed in its congener, B. cavaticus. This study provides comprehensive biological, ecological, and behavioral insights into the new species, along with details about its conservation status and associated threats.